Functional properties of the Su(Hw) complex are determined by its regulatory environment and multiple interactions on the Su(Hw) protein platform - L. S. Melnikova; M. V. Kostyuchenko; V. V. Molodina; P. G. Georgiev; A. K. Golovnin (Вавиловский журнал генетики и селекции)
The Su(Hw) protein was first identified as a DNA-binding component of an insulator complex in Drosophila. Insulators are regulatory elements that can block the enhancer-promoter communication and exhibit boundary activity. Some insulator complexes contribute to the higher-order organization of chromatin in topologically associated domains that are fundamental elements of the eukaryotic genomic structure. The Su(Hw)-dependent protein complex is a unique model for studying the insulator, since its basic structural components affecting its activity are already known. However, the mechanisms involving this complex in various regulatory processes and the precise interaction between the components of the Su(Hw) insulators remain poorly understood. Our recent studies reveal the fine mechanism of formation and function of the Su(Hw) insulator. Our results provide, for the first time, an example of a high complexity of interactions between the insulator proteins that are required to form the (Su(Hw)/Mod(mdg4)-67.2/CP190) complex. All interactions between the proteins are to a greater or lesser extent redundant, which increases the reliability of the complex formation. We conclude that both association with CP190 and Mod(mdg4)-67.2 partners and the proper organization of the DNA binding site are essential for the efficient recruitment of the Su(Hw) complex to chromatin insulators. In this review, we demonstrate the role of multiple interactions between the major components of the Su(Hw) insulator complex (Su(Hw)/Mod(mdg4)-67.2/CP190) in its activity. It was shown that Su(Hw) may regulate the enhancer–promoter communication via the newly described insulator neutralization mechanism. Moreover, Su(Hw) participates in direct regulation of activity of vicinity promoters. Finally, we demonstrate the mechanism of organization of “insulator bodies” and suggest a model describing their role in proper binding of the Su(Hw) complex to chromatin.